RELIGIOSITY AND DATING DECISION-MAKING AMONG INDONESIAN PSYCHOLOGY UNDERGRADUATES: A CORRELATIONAL STUDY - Tengku Nuranasmita; Anna Wati Dewi Purba; Baniah Hasibuan (CV. TOTUS TUUS, 2026)
Dating has become a salient developmental and social phenomenon among university students, yet its expression may be shaped by internalized religious values that guide moral reasoning and self-control. This study examined the relationship between religiosity and dating decisions among Psychology students at the University of Medan Area. Using a quantitative correlational design, data were collected from a purposive sample of active students (N = 177) via two instruments: a Religiosity Scale and a Dating Decision Scale. Both instruments demonstrated excellent internal consistency (Cronbach’s alpha = 0.983 and 0.987, respectively). Assumption testing indicated normal distributions for both variables and evidence of linearity between them. Pearson product–moment analysis revealed a strong, significant negative association between religiosity and dating decisions (r = −0.855, p < 0.001), with a coefficient of determination (R²) of 0.731, indicating that religiosity accounted for 73.1% of the variance in dating decisions. Mean comparisons further suggested that students’ religiosity was relatively low, whereas their tendency toward dating decisions was relatively high. The principal conclusion is that higher religiosity is associated with lower dating decision tendencies among students. These findings imply that strengthening the internalization of religious and ethical values—integrated with counseling and student development programming—may support more reflective personal decision-making in campus life. Future research should examine mediating and moderating factors (e.g., peer influence, self-control, gender, and social media exposure) and employ longitudinal or mixed-method approaches.